Low-cost nanomaterials : toward greener and more efficient energy applications - Wang, Jun; Lin, Zhiqun (Green Energy and Technology, 2014)
This book will cover the most recent progress on the use of low-cost nanomaterials and development of low-cost/large scale processing techniques for greener and more efficient energy related applications, including but not limited to solar cells, energy storage, fuel cells, hydrogen generation, biofuels, etc. Leading researchers will be invited to author chapters in the field with their expertise. Each chapter will provide general introduction to a specific topic, current status of research and development, research challenges, and outlook for future direction of research. This book aims to benefit a broad readership, from undergraduate/graduate students to researchers working on renewable energy.